Trace-level analysis of genotoxic sulfonate ester impurities in teneligliptin by GC-MS - Murugan Maniavannan, Palaniappan Ilayaraja, Paramasivam Parthiban, (Journal of Applied Pharmaceutical Science, 2022)
The formation of various sulfonate esters is unavoidable during the synthesis of teneligliptin (TEN), an important drug of type 2 diabetes mellitus. They are essentially to be eliminated from the drug due to their potential genotoxic nature, but there are no effective methods in practice. Hence, we developed an efficient method to get rid of those genotoxic impurities from the drug. The successfully developed method was validated for the trace-level analysis of methyl 1-octanesulfonate (MOS), ethyl 1-octanesulfonate (EOS), and butyl 1-octanesulfonate (BOS) in TEN by gas chromatography-mass spectrometry, in terms of detection limit (LOD), quantification limit (LOQ), precision, accuracy, linearity, robustness, and specificity. The LOD and LOQ values are 0.74, 0.68, and 0.61 ppm and 2.48, 2.25, and 2.03 ppm, respectively, for MOS, EOS, and BOS. The approach was linear in the LOQ of 56 ppm with the correlation coefficient of 0.9979 and above. The average %recovery of residual sulfonate esters from the drug was 94.5 (MOS), 97.5 (EOS), and 97.2 (BOS). The developed method is suitable for even trace-level quantification of MOS, EOS, and BOS content in TEN.
Keywords: Octanesulfonate, sulfonate ester, genotoxic impurity, teneligliptin, GC-MS